Economy and Ecology in the Iberian Cork Oak Forests: Land Use in the Second Half of the 19th Century - Faísca, Carlos Manuel (2020)
The supply of raw material is probably the most important issue in the cork business, mainly due to its preponderance in the industry cost structure. This article analyses, from a comparative perspective between Spain and Portugal, a practice with a high repercussion in the cork production, the use of the soil. The main goal is to identify, in the late 19th century, agroforestry practices that reduced the cork potential of any of the countries, helping recognize a factor that can explain the gap in the level of development of the cork sector in Spain and Portugal. However, it is concluded that there were constant harmful actions against cork development in both countries. Soil mobilization and extraction of plants, often due to cereal cultivation, led to a decline in soil fertility with a negative economic and ecological impact.